Understanding parricide when sons and daughters kill parents - Heide, Kathleen M. (New York : Oxford University Press, 2013)
This study is about juvenile and adult sons and daughters who kill their parents. It moves far behind the statistical correlates of parricide by synthesizing the professional literature on parricide in general, matricide, patricide, double parricides, and familicides. The book explains the reasons behind the killings and includes in-depth discussion of issues related to prosecuting and defending parricide offenders. The book is enriched with its focus on clinical assessment, case studies, and follow-up of parricide offenders, as well as treatment, risk assessment, and prevention.
Description based on online resource; title from home page (viewed on Jan. 7, 2013).
Includes bibliographical references and index.
Keywords: Parricide; Family violence; Abused children; Mentally ill children -- Care; Juvenile homicide; Parricide -- Case studies; Family violence -- Case studies; Abused children -- Case studies; Mentally ill children -- Care -- Case studies; Juvenile homicide -- Case studies